2017
DOI: 10.1093/ntr/ntx057
|View full text |Cite
|
Sign up to set email alerts
|

Day-to-Day Variability in Self-Reported Cigarettes Per Day

Abstract: Across day variability in CPD is larger than implied in prior studies. Determining causes of day-to-day variability should increase our understanding of the determinants of smoking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 25 publications
2
11
0
Order By: Relevance
“…This methodological weakness was only partially compensated for by the interview discussion of Adrian's evening tobacco use situations. These findings are in line with previous studies reporting a high variability in cigarettes smoked per day among a substantial subset of smokers (e.g., Hughes et al 2017). In fact, variability may be even more pronounced among light and intermittent smokers (Shiffman et al 2012), which is consistent with the smoking behavior reported by Adrian.…”
Section: Discussionsupporting
confidence: 93%
“…This methodological weakness was only partially compensated for by the interview discussion of Adrian's evening tobacco use situations. These findings are in line with previous studies reporting a high variability in cigarettes smoked per day among a substantial subset of smokers (e.g., Hughes et al 2017). In fact, variability may be even more pronounced among light and intermittent smokers (Shiffman et al 2012), which is consistent with the smoking behavior reported by Adrian.…”
Section: Discussionsupporting
confidence: 93%
“…The number of cigarettes smoked per day (printed pre-prepared cigarette diary brought to the TMS lab for each session) [32] was evaluated by subjective self-report. The subject recorded their daily cigarette use each morning before each rTMS session and every morning during the 1-month follow-up.…”
Section: Evaluation Of Cigarette Consumption Nicotine Dependence Cued Craving and Biomarkersmentioning
confidence: 99%
“…Within-person variability in CPD was measured via the coefficient of variation (within-person standard deviation of cigarettes across days divided by the within-person mean) consistent with a method used by Hughes et al 40 For this analysis, those without variability in CPD (n = 11) were assigned a coefficient of variation of zero. A t-test was used to test the difference between male and female average coefficient of variation (Hypothesis 4).…”
Section: Data Analytic Proceduresmentioning
confidence: 99%